Educational leadership : performance & improvement - Lope Pihie, Zaidatol Akmaliah (Universiti Putra Malaysia Press, 2012)
Focusing on educational leadership, this book attempts to provide a fertile ground for research and practice in education systems in order to develop qualified and competent students for their future life and workspace. Although different in focus, various chapters of this book aim to open new windows to improving educational leadership and offering students more effective educational environments. Educational Leadership:Performance and Improvement is designed into ten chapters each of which related to a critical topic in educational leadership.